MOA-2007-BLG-197: Exploring the brown dwarf desert - Ranc, C.; Cassan, A.; Albrow, M.; Kubas, D.; Bond, I.; Batista, V.; Beaulieu, J.; Bennett, D.; Dominik, M.; Dong, S.; Fouqué, P.; Gould, A.; et al. (EDP Sciences, 2015)
© ESO 2015. We present the analysis of MOA-2007-BLG-197Lb, the first brown dwarf companion to a Sun-like star detected through gravitational microlensing. The event was alerted and followed-up photometrically by a network of telescopes from the PLANET, MOA, and µFUN collaborations, and observed at high angular resolution using the NaCo instrument at the VLT. From the modelling of the microlensing light curve, we derived basic parameters such as, the binary lens separation in Einstein radius units (s ? 1:13), the mass ratio q = (4:732 ± 0:020) × 10-2 and the Einstein radius crossing time (tE ? 82d). Because of this long time scale, we took annual parallax and orbital motion of the lens in the models into account, as well as finite source effects that were clearly detected during the source caustic exit. To recover the lens system's physical parameters, we combined the resulting light curve best-fit parameters with (J, H, Ks) magnitudes obtained with VLT NaCo and calibrated using IRSF and 2MASS data. From this analysis, we derived a lens total mass of 0:86 ± 0:04 M? and a lens distance of DL = 4:2 ± 0:3 kpc. We find that the companion of MOA-2007-BLG-197L is a brown dwarf of 41 ± 2 MJ observed at a projected separation of a? = 4:3 ± 0:1 AU, and orbits a 0:82 ± 0:04 M? G-K dwarf star. We then placed the companion of MOA-2007-BLG-197L in a mass-period diagram consisting of all brown dwarf companions detected so far through different techniques, including microlensing, transit, radial velocity, and direct imaging (most of these objects orbit solar-type stars). To study the statistical properties of this population, we performed a two-dimensional, non-parametric probability density distribution fit to the data, which draws a structured brown dwarf landscape. We confirm the existence of a region that is strongly depleted in objects at short periods and intermediate masses (P ? 30 d, M ~ 30-60 MJ), but also find an accumulation of objects around P ~ 500 d and M ~ 20 MJ, as well as another depletion region at long orbital periods (P ? 500 d) and high masses (M ? 50 MJ). While these data provide important clues on the different physical mechanisms of formation (or destruction) that shape the brown dwarf desert, more data are needed to establish their relative importance, in particular as a function of host star mass. Future microlensing surveys should soon provide more detections, in particular for red dwarf hosts, thus uniquely complementing the solar-type host sample.